2022
DOI: 10.3389/fpls.2022.1030140
|View full text |Cite
|
Sign up to set email alerts
|

Short-term severe drought influences root volatile biosynthesis in eastern white pine (Pinus strobus L)

Abstract: Climate change-related drought stress is expected to shift carbon partitioning toward volatile organic compound (VOC) biosynthesis. The effect of drought stress on VOC synthesis remains unknown in several tree species. Therefore, we exposed eastern white pine (Pinus strobus) plants to severe drought for 32 days and performed physiological analysis (chlorophyll content, leaf water content, and root/shoot index), biochemical analysis (non-structural carbohydrates, proline, lipid peroxidation, and antioxidant ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 89 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…Once drought ceased, C allocation to storage was still prioritized at the expense of growth [ 46 ]. Severe drought treatment largely reduced photosynthetic carbon assimilation [ 47 ]. Plants may have allocated more NSC from source organs to roots [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Once drought ceased, C allocation to storage was still prioritized at the expense of growth [ 46 ]. Severe drought treatment largely reduced photosynthetic carbon assimilation [ 47 ]. Plants may have allocated more NSC from source organs to roots [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the expression of CfCHLM in C. fortunei was shown to be downregulated under abiotic stress, and the downregulation of the CHLM gene may have inhibited the synthesis of chl. Many studies have shown that the synthesis of chl is inhibited under various abiotic stresses [28][29][30][31], which demonstrates the downregulation of the CfCHLM gene in response to stress.…”
Section: Functional Analysis and Expression Pattern Of Cfchlmmentioning
confidence: 99%
“…This research should develop, analyze, and integrate detailed models of the biosynthetic pathways for those terpenoids with the MVA and MEP pathway models. That development and integration should take into account that certain terpenoids are synthesized using material that is drawn mainly from only one of the pathways (Qiao et al, 2021;Yang et al, 2012;Rodríguez-Concepción et al, 2004;Wu et al, 2021;Chandrasekaran et al, 2022;Liu et al, 2024). MVA-derived isoprenoid end products in plants are sterols and cytokinins that modulate membrane architecture, plant growth and development, and brassinosteroids that work as steroid hormones.…”
Section: Limitations Of This Workmentioning
confidence: 99%